Weaning calves early - M. McKee; K.K. Bolsen; K.L. Conway; G. Fink; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1974)
An 85-day, post weaning growth rate for 30 calves weaned at an average age of 110.5 days was compared with the growth rate of 30 calves nursing their mothers the same period. Average age of the nursing calves at the start of the test was 106.2 days. All calves received creep feed free-choice. The early weaned calves were divided into two groups; one group (A) received direct-cut alfalfa wilted with rolled milo free-choice; the other (B), field-wilted haylage plus rolled milo free-choice. Twenty-four of the later weaned calves were confined to dry lot with their mothers, and 6 (D) nursed their mothers on pasture. Average daily gains (lbs.) and feed costs per pound of gain for the calves in groups A through D, respectively, were: 2.97. $0.232; 2.50, $0.254; 3.03, $0.309 and 2.87, $0.229. Feed cost per pound of gain was computed by combining 85 day feed cost of cow and calf and dividing by the calves gain.
Keywords: Cattlemen' s Day; 1974; Report of progress (Kansas State University. Agricultural Experiment Station); 210; Beef; Weaning; Growth rate